Stereoselective Synthesis of (Z)-2-Bromo-2-CF3-Vinyl Phenyl Sulfide and its Sonogashira Cross-Coupling Reaction - Fukuda, Yui; Kikumura, Takumi; Sakoda, Saki; Ikeda, Genki; Nakamura, Yuki; Dojyo, Masakazu; Yamada, Yasunori; Hanamoto, Takeshi (Synlett, 2019)
A practical synthesis of (Z)-2-bromo-2-CF3-vinyl phenyl sulfide from 2-CF3-vinyl phenyl sulfide was achieved using bromine (Br2) in the presence of LiBr and LiOAc in AcOH in one flask. This method affords a stereodefined product in high yield under mild conditions. The synthetic application of the product was briefly examined, providing a wide range of Sonogashira cross-coupling products using terminal acetylenes as a coupling partner.
Keywords: organofluorine; trifluoromethyl group (CF3); bromoalkene; vinyl sulfide; stereoselective; Sonogashira cross-coupling